Quality of water recovered by treating acid mine drainage using pervious concrete adsorbent - Shabalala, AN; Ekolu, SO (Water SA, 2019)
In this paper, a batch experiment was conducted to evaluate the water quality obtained from using pervious concrete (PERVC) technology to treat acid mine drainage (AMD). The study proposes an innovative application of PERVC as a permeable reactive barrier liner in evaporation ponds. The effectiveness of PERVC adsorbent in removing heavy metals was compared with that of zero-valent iron (ZVI) of particle size 1.0 to 1.8 mm. The AMD used in the study was obtained from abandoned gold and coal mines. PERVC mixtures consisted of granite aggregate and ordinary Portland cement CEM I 52.5R (CEM I) or CEM I containing Class F 30% fly ash (30%FA) as a cement replacement material. ZVI was prepared from a mixture of silica sand and iron grit of specific sizes. PERVC and ZVI media were used to conduct batch reactor tests with AMD, for a period of 43 days at a ratio of 1 L of reactive material to 3 L of AMD. The quality of treated AMD was compared against effluent discharge standards. The contaminants Al, Fe and Zn were effectively removed by both PERVC and ZVI. Also, both adsorbents reduced Ni, Co and Cu to levels below those measured in raw AMD. However, PERVC was more effective in removing Mn and Mg while ZVI was ineffective. Although PERVC removed more heavy metals and with greater efficiency than ZVI, the PERVC-treated water showed high pH levels and exhibited elevated Cr6+ concentrations, owing to leaching from the cement and fly ash materials used in PERVC mixtures.